1982
DOI: 10.1002/jcp.1041100213
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator: The major secreted neutral protease of cultured skeletal muscle cells

Abstract: Clonal mouse skeletal muscle cells which differentiate in culture and form synapses with neuronal cells were found to secrete high levels of protease activity as measured with an 125I-fibrin assay. The secreted proteolytic activity was more than 90% dependent upon the presence of plasminogen in the medium, and had a pH optimum at 7 to 8. This activity was not inhibited by n-ethylmaleimide, pepstatin, EDTA, or EGTA. At millimolar concentrations, greater than 90% inhibition was obtained with either soybean tryps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 23 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…Plasminogen-independent activity was barely above the zero value even after 6 hr of incubation (data not shown). Using the 125I-labeled fibrin plate assay (28), previous studies with neutral proteases secreted from G8-1 clonal mouse muscle cells (17) and rat muscle in organ culture (B.W.F. and J.S.R., unpublished work) had indicated considerable PA activity, but plasminogen-independent activity was also detected, especially in muscle homogenates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasminogen-independent activity was barely above the zero value even after 6 hr of incubation (data not shown). Using the 125I-labeled fibrin plate assay (28), previous studies with neutral proteases secreted from G8-1 clonal mouse muscle cells (17) and rat muscle in organ culture (B.W.F. and J.S.R., unpublished work) had indicated considerable PA activity, but plasminogen-independent activity was also detected, especially in muscle homogenates.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16], PAs might also play a role in the neuromuscular system. Previous studies indicated that PA was the predominant neutral protease secreted by cultured clonal murine skeletal muscle cells (17). More recent studies have shown that denervation is followed by a dramatic increase in adult mouse muscle PA activity (18).…”
mentioning
confidence: 98%
“…This is controversial for the 72 kDa gelatinase for which both plasmin-dependent (Keski-Oja et al, 1992) and plasmin-independent (Strongin et al, 1993) routes of activation have been described. Human skeletal muscle satellite cells have been shown to express plasminogen activator (Quax et al, 1992) as have murine skeletal muscle cells and cell lines (Festoff et al, 1982;Hantai et al, 1989;Mayer et al, 1986;Miskin et al, 1978). We therefore investigated the ability of satellite cell-conditioned medium to stimulate plas- were not made since their mRNAs were essentially undetectable in untreated cells (see Fig.…”
Section: Latency Of the 72 Kda Gelatinasementioning
confidence: 99%
“…These include interstitial (type I) collagenase (or MMP-1) (Harris et al, 1984), 72 kDa gelatinasekype JV collagenase (MMP-8) (Collier et al, 1988), 92 kDa gelatinaseltype IV collagenase (MMP-9) (Wilhelm et al, 1989), and stromelysin-1 (MMP-3), which can degrade proteoglycans, fibronectin, laminin, gelatin, and certain of the collagens (Wilhelm et al, 1987;Murphy et al, 1987;Matrisian, 1992). The only neutral matrix-degrading protease presently known to be secreted by muscle cells is plasminogen activator (Miskin et al, 1978;Festoff et al, 1982;Quax et al, 1992). Increased activity of urokinase-type plasminogen activator has been detected following denervation of adult mouse muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, whereas the effects of the extracellular environment impact myogenesis, it is also acknowledged that skeletal muscle may also function as the largest endocrine organ in humans for secreting extracellular factors, including myokines that regulate muscle development (52,53). Apart from the well-known myokines, such as members of the insulin-like growth factor-1 (54 -63) and transforming growth factor (TGF) families (64 -72), there are studies investigating other myokines, such as plasminogen activator (73), collagenase (74), decorin (75), glial growth factor (76), neurocrescin (77), meltrin ␣ (78), musculin (52,79), interleukin-1 ␤ (80), interleukin-7 (81), ADAMTS-like 2 (82), Fstl-1 (83), and secreted protein acidic and rich in cysteine (SPARC) (84 -86). To advance our understanding of secreted proteins in an unbiased manner, we have undertaken a comprehensive "discovery" approach to initially identify and quantify components of the secretome.…”
mentioning
confidence: 99%